Challenges in Sustaining Donor Initiated Monitoring and Evaluation System for HIV and AIDS at the Service Delivery Level; Examples from APHIA plus project in Kakamega County - Odiga, Leonard Yosi; Onyango, Leah; Pido, Odoch (Advances in Social Sciences Research Journal, 2024)
HIV/AIDS remains a major global public health issue, with Sub-Saharan Africa being the hardest hit and housing over 1.7 million people living with HIV. Kenya’s long-term success in combating AIDS requires decentralization, allowing counties and local networks to take an active role in developing, implementing, and monitoring evidence-based initiatives. Current frameworks for Monitoring and Evaluating (M&E) HIV/AIDS programs are primarily focused on data collection to inform decisions at the county and national levels. As a result, there’s a pressing need to boost M&E capacity at the service delivery level to ensure effective HIV/AIDS programs. This paper interrogates the AIDS, Population, and Health Integrated Assistance (APHIA plus) Western Project’s success in enhancing local M&E capacity at the service delivery level in Kakamega County and the challenges of sustaining the gains beyond the project period. The study sampled 110 health facilities offering HIV/AIDS services in Kakamega County. and established It established that the APHIAplus Western Project made significant strides in strengthening the M&E system by establishing M&E departments, improving collection, quality and dissemination of M&E data and hiring trained staff. The study identified the main challenges to the sustainability of the M&E system which included heavy reliance on external funding and inadequate dedicated M&E staff in county health facilities where 62% of staff carrying out M&E functions/duties were hired by the project. It also identified a challenge in the likely compromise to the prerequisites for quality M&E data after the exit of the project since there was no clear transition plan from project to county. The study results indicate that that 70% of the facilities were collecting monthly data using specified tools and storing the data in an automated system. ANOVA yields a statistically significant difference in the length of years the APHIAplus Western project has supported the health facilities and the frequency of M&E data collection at the service delivery level. The study further identified a challenge in the likely discontinuation of fora/platforms organized monthly in 94% of the facilities for dissemination of M&E findings and supported by APHIAplus Western Project. The study recommends increasing the number of dedicated M&E staff in county health facilities by developing a phased transition plan for M&E staff contracted by the project with a clear handover schedule to County Government of Kakamega, and advocating for increased budget allocation for M&E activities at the service delivery level. Additionally, health facilities are encouraged to explore strategies for diversifying funding sources for M&E activities.